2020
DOI: 10.21203/rs.3.rs-107391/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Tobacco Smoking Status on Morbidity and Mortality in Patients Hospitalized with COVID-19 Pneumonia: Observational study

Abstract: Background: Determine the impact of tobacco smoking status on patients hospitalized with COVID-19 pneumonia in the need for ICU care, mechanical ventilation and mortality. Methods: We performed a retrospective cohort study, that involved chart review. All adults 18 years or older with a diagnosis of COVID-19 pneumonia hospitalized from March 15th, 2020 to May 06th, 2020 with a positive reverse transcription polymerase chain reaction (RT-PCR) nasopharyngeal swab for COVID-19. We used chi-squared test for catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Multiple studies noted the high correlation between a history of smoking and increased comorbidities, as well as the association between multiple comorbidities and increased risk of negative COVID-19 outcomes [25,[30][31][32][33][34]. One study that compared smokers, diabetics, and diabetics who smoke found significantly worse outcomes, including increased risk of death, for the diabetics who smoke compared to the other groups [27].…”
Section: Journal Of Smoking Cessationmentioning
confidence: 99%
“…Multiple studies noted the high correlation between a history of smoking and increased comorbidities, as well as the association between multiple comorbidities and increased risk of negative COVID-19 outcomes [25,[30][31][32][33][34]. One study that compared smokers, diabetics, and diabetics who smoke found significantly worse outcomes, including increased risk of death, for the diabetics who smoke compared to the other groups [27].…”
Section: Journal Of Smoking Cessationmentioning
confidence: 99%